COMMUNICATION STRATEGIES IN PUBLIC MANAGEMENT AND ADMINISTRATION - YERMOLENKO, Oksana; MELNYK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article shows that communication in administrative systems has a public and legal purpose and regulates the movement of individual administrative subjects to the social community while preserving a certain degree of autonomy, independence, self-determination, and individuality of these subjects. The authors emphasize that regardless of the form of communication, the communication process plays a vital role in public administration. It was found that communication processes in public administration include elements such as administrative bodies and communities, communications, messages, information barriers, and feedback. It was determined that if the external communication of state administration is aimed at influencing civil society, receiving recommendations from society representatives, and adjusting positions, internal communication absorbs the entire administrative system from the inside and is the primary driving force in making major management decisions. It turned out to be a key driving force in management decision-making. This article analyzes the properties of communications in public administration. It is noted that communication is the exchange of information between two subjects. For public administration bodies, feedback is an essential element of communication activity, which emphasizes the transition from one-way notification of citizens about government actions to two-way communication - "civil society - government - civil society". It has been demonstrated that communication should ensure the effective exchange of information between the subject of management and the object of management, establish communication channels for the exchange of information between individual personnel and groups, adjust and arrange information flows to improve relations between communication subjects at different levels in the process of information exchange. It is emphasized that there are many different communication channels in the administrative system, and it is difficult to determine which are the most important and necessary.